Interval travel times for robust synchronization in city logistics vehicle routing. (November 2020) - Groß, Patrick-Oliver; Ehmke, Jan Fabian; Mattfeld, Dirk Christian
Highlights: Complete information flow to consider travel time uncertainty in city logistics vehicle routing. An innovative approach for robust routing in city logistics. Applicability of interval travel times in conjunction with min–max regret evaluation. Comprehensive case study based on real-world data for a representative city logistics vehicle routing setting. Computational results show alternatives that are more robust, but also cost efficient. Abstract: We propose a consistent information flow to integrate Interval Travel Times (ITT) into a city logistics vehicle routing problem with satellites. The consistent information flow encompasses the derivation of ITT, the usage of ITT in robust shortest path computation and the integration of ITT into robust vehicle routing. Based on the results of the information flow, robust meeting times of first-tier and second-tier vehicles are created. We evaluate the approach with large real-world traffic data sets. We observe that the integration of ITT leads to first-tier routes that are reasonably efficient and robust.